Magnetosheath waves under very low solar wind dynamic pressure: Wind/Geotail observations - Farrugia, C.J. (2005)
The expanded bow shock on and around "the day the solar wind almost disappeared" (11 May 1999) allowed the Geotail spacecraft to make a practically uninterrupted 54-h-long magnetosheath pass near dusk (16:30-21:11 magnetic local time) at a radial distance of 24 to 30 RE (Earth radii). During most of this period, interplanetary parameters varied gradually and in such a way as to give rise to two extreme magnetosheath structures, one dominated by magnetohydrodynamic (MHD) effects and the other by gas dynamic effects. We focus attention on unusual features of electromagnetic ion wave activity in the former magnetosheath state, and compare these features with those in the latter. Magnetic fluctuations in the gas dynamic magnetosheath were dominated by compressional mirror mode waves, and left-and right-hand polarized electromagnetic ion cyclotron (EIC) waves transverse to the background field. In contrast, the MHD magnetosheath, lasting for over one day, was devoid of mirror oscillations and permeated instead by EIC waves of weak intensity. The weak wave intensity is related to the prevailing low solar wind dynamic pressures. Left-hand polarized EIC waves were replaced by bursts of right-hand polarized waves, which remained for many hours the only ion wave activity present. This activity occurred when the magnetosheath proton temperature anisotropy (=Tp, ⊥/Tp, ∥-1) became negative. This was because the weakened bow shock exposed the magnetosheath directly to the (negative) temperature anisotropy of the solar wind. Unlike the normal case studied in the literature, these right-hand waves were not by-products of left-hand polarized waves but derived their energy source directly from the magnetosheath temperature anisotropy. Brief entries into the low latitude boundary layer (LLBL) and duskside magnetosphere occurred under such inflated conditions that the magnetospheric magnetic pressure was insufficient to maintain pressure balance. In these crossings, the inner edge of the LLBL was flowing sunward. The study extends our knowledge of magnetosheath ion wave properties to the very low solar wind dynamic pressure regime. © European Geosciences Union 2005.